The researching of antipyretic effect for new S-derivatives 1,2,4-triazoles with morpholinomethylene fragment - R. О. Shcherbyna (The State Expert Center of the Ministry of Health of Ukraine, 2018)
It is known that high temperature is a sign or a symptom of the disease. In order to struggle with this disease there are actively used antipyretics. Importantly, this class of drugs along with analgesic and antiinflammatory properties is also exhibits a sufficiently wide range of side effects. Therefore, the search for drugs with high antipyretic activity and low toxicity is very important and actual. Suffice it interesting and promising in this direction are 1,2,4-triazole thioderivatives. The aim of this research was the pharmacological screening of antipyretics among 4-R-3-(morpholinomethylene)-1,2,4-triazole-5-thiones alkyl derivatives which were synthesized for the first time. Experimental fever was reproduced on white non-linear rats by administration of 2,4-dinitrophenol in a dose of 20 mg/kg. As reference agent was used an acetylsalicylic acid at 100 mg/kg. The study found that the compounds that were being studied, and the comparison drug had different effects on body temperature in rats. Thus, among investigated compounds the most active is 3-(morpholinomethylene)-5-decylthio-4-ethyl-4H-1,2,4-triazole (ПКР-227) and its ability to inhibit hyperthermia was more than acetylsalicylic acid and it reduces the temperatures on 2,86 ºC body rats (p ≤ 0,05). Hydrocarbon chain residue elongation at position C5 of 1,2,4-triazole nucleus increases antipyretic activity of the synthesized compounds. Substitution of the phenyl to ethyl radical at the nitrogen atom N4 in the molecules of 4-R-3-(morpholinomethylene)-1,2,4-triazole-5-thiones alkyl derivatives increases antipyretic effect of the synthesized compounds. The obtained results may be used for further new pharmacological tests of 1,2,4-triazole derivatives.